Dietary Fat Intake and Individual Double Burden of Malnutrition in the form of Obesity and Anemia among Indonesian Adolescents - Siti Aminah; Qonita Rachmah; Soraya Tri Widayani; Azizah Ajeng Pratiwi; Trias Mahmudiono (Universitas Airlangga, 2026)
This study assessed the correlation between saturated fat intake and the double burden of malnutrition (DBM) among Indonesian adolescents, specifically focusing on obesity and anemia. The research examined the prevalence of DBM and its association with saturated fat consumption in this population. Anemia was collected using a finger-pick, a Semi-quantitative Food Frequency Questionnaire (SFFQ) was employed to analyze the dietary intake. Data analysis univariately and regression for bivariate analysis. Six hundred and twenty-one adolescents were collected for anemia screening, and only 107 completed dietary assessments. Adolescent girls who live alone and have lower food expenses are more risk to DBM. The results found that overall fat intake was significantly linked to the occurrence of DBM in Indonesian adolescents, with those consuming higher levels of fat being more likely to experience both obesity and anemia simultaneously. This finding highlights the complex nutritional challenges faced by developing countries, where both overnutrition and undernutrition coexist. The study emphasizes the importance of limiting fat intake, and reducing the prevalence of DBM among adolescents in Indonesia.